Prognostic role of low QRS voltages in patients with cardiac amyloidosis. (3rd October 2022) - Guerra, F; Coretti, F; Torselletti, L; Coraducci, F; Belleggia, S; Manfredi, R; Silenzi, M; Falanga, U; Principi, S; Stronati, G; Ciliberti, G; Barbarossa, A; et al.
Abstract: Introduction: Cardiac amyloidosis (CA) is an underdiagnosed and heterogeneous cardiac disease characterized by the extracellular deposition of misfolded proteins in the cardiac tissue. Clinical manifestations are heterogeneous leading to progressive heart failure, often complicated by arrhythmias and conduction system disease. Among several sign and symptoms that are suspicious for the disease, named "red flags", disproportionally low QRS voltages on the ECG has been described. Purpose: The aim of this prospective observational study is to evaluate potential prognostic features of QRS amplitude in AL e ATTR CA patients. Methods: All consecutive patients admitted to the Cardiomyopathy Clinic of our institution have been enrolled after receiving CA diagnosis, according to the current guidelines. We included all patients ≥18 years with a diagnosis of CA and written informed consent. A complete assessment including a standard 12-lead electrocardiogram (ECG) and echocardiogram was performed at enrollment. Low QRS voltages (LQRSV) was defined as a QRS total amplitude of ≤5 mm in every limb leads and ≤10 mm in every precordial lead. LQRSV was tested as an independent predictor of death from all causes (primary endpoint), hospitalization from cardiovascular causes, ventricular and supraventricular arrhythmias. Results: Sixty patients (46 males, 77±12 years old) were enrolled, of which 18 (30%) met the criteria for LQRSV. Patients with LQRSV presented more frequently with an history of ventricular arrhythmia (27.8% vs. 6.7%, p=0.04), a lower left ventricular diastolic volume (31±7 vs. 44±18 ml/m 2 ; p=0.04), and higher retinol-binding-protein 4 (9.3±2.2 vs 3.2±1.5 mg/dl; p=0.02). No differences were seen in the primary outcome (46% vs. 50%; p=NS; Figure 1) or in the secondary ones (cardiovascular hospitalization 25% vs. 21%; ventricular arrhythmias 12% vs 4%; supraventricular arrhythmias 29% vs 19%; all p=NS) between the two groups during a median follow up of 1.1 year. Conclusions: In the present cohort of CA patients LQRSV did not emerge as independent predictor of all-cause mortality at 1 year. Although LQRSV is a recognized diagnostic "red-flag" in the work-up of CA, its role as prognostic marker remains unclear. Further studies with a longer follow-up are needed to better define the prognostic role of LQRSV among CA patients. Funding Acknowledgement: Type of funding sources: None.